PENERAPAN DICTOGLOSS BERBASIS BLOG UNTUK MENINGKATKAN HOTS PESERTA DIDIK PADA MATA PELAJARAN BAHASA JEPANG - Handayani, Herlina Putri (Universitas Negeri Jakarta, 2020)
In the rapid of global competition, human that has intelligence and creative skills are demanded. Therefore, students need to be prepared with high order thinking skills (HOTS). In the second language acquisition theory, there are input theory and output theory. Dictogloss is a technique that applies these two activities together, where input and output are applied continuously. This study aims to find out whether the application of the dictogloss technique in Japanese learning can increase the students’ high order thinking skills. This study implemented classroom action research which conducted in two cycles. This study revealed the following findings: (1) students’ high order thinking skills increased into 40% in second cycle, (2) students’ average grade increased into 83, (3) students’ completeness which higher than passing grade learning standard increased into 85%. Based on the results, in can be concluded that the application of blog-based dictogloss can increase the students’ HOTS in Japanese lesson.